Comportamiento fenológico de un bosque pluvial de premontano en Cataratitas de San Ramón, Costa Rica - Ortiz V., Rodolfo; Fournier O., Luis Alberto (Revista de Biología Tropical, 1983)
This work reports 15 months of phenological observations in a premontane rainforest of Costa Rica. All phenological characteristics display annual periodicity. The peak of leaf flushing occurs during the driest months of the year, but flowering shows two peaks, one m April (dry season) and the other in August (wet season). On the other hand, fruiting and leaf-fall show maximum activity during the wet season. A significative correlation between rainfall and temperature with leaf flushing for the three tree strata was found. Leaf fall and flowering of codominant and dominated trees correlate with rainfall, but this is not true for dominant trees.